Recent rapid rise of a permethrin knock down resistance allele in Aedes aegypti in México - Kittayapong, Pattamaporn; Ponce García, Gustavo; Flores Suárez, Adriana Elizabeth; Fernández Salas, Ildefonso; Saavedra Rodríguez, Karla Lizet; Reyes Solis, Guadalupe del Carmen; Lozano Fuentes, Saúl; Guillermo Bond, J.; Casas Martínez, Mauricio; Ramsey, Janine M.; García Rejón, Julián Everardo; Domínguez Galera, Marco Antonio; et al. (Public Library of Science, 2009)
Background: Aedes aegypti, the ‘yellow fever mosquito’, is the primary vector to humans of dengue and yellow fever flaviviruses (DENV, YFV), and is a known vector of the chikungunya alphavirus (CV). Because vaccines are not yet available for DENV or CV or are inadequately distributed in developing countries (YFV), management of Ae. aegypti remains the primary option to prevent and control outbreaks of the diseases caused by these arboviruses. Permethrin is one of the most widely used active ingredients in insecticides for suppression of adult Ae. aegypti. In 2007, we documented a replacement mutation in codon 1,016 of the voltage-gated sodium channel gene (para) of Ae. aegypti that encodes an isoleucine rather than a valine and confers resistance to permethrin. Ile1,016 segregates as a recessive allele conferring knockdown resistance to homozygous mosquitoes at 5–10 mg of permethrin in bottle bioassays. Methods and Findings: A total of 81 field collections containing 3,951 Ae. aegypti were made throughout Me´xico from 1996 to 2009. These mosquitoes were analyzed for the frequency of the Ile1,016 mutation using a melting-curve PCR assay. Dramatic increases in frequencies of Ile1,016 were recorded from the late 1990’s to 2006–2009 in several states including Nuevo Leo´n in the north, Veracruz on the central Atlantic coast, and Yucata´n, Quintana Roo and Chiapas in the south. From 1996 to 2000, the overall frequency of Ile1,016 was 0.04% (95% confidence interval (CI95) = 0.12%; n = 1,359 mosquitoes examined). The earliest detection of Ile1,016 was in Nuevo Laredo on the U.S. border in 1997. By 2003–2004 the overall frequency of Ile1,016 had increased ,100-fold to 2.7% (60.80% CI95; n = 808). When checked again in 2006, the frequency had increased slightly to 3.9% (61.15% CI95; n = 473). This was followed in 2007–2009 by a sudden jump in Ile1,016 frequency to 33.2% (61.99% CI95; n = 1,074 mosquitoes). There was spatial heterogeneity in Ile1,016 frequencies among 2007–2008 collections, which ranged from 45.7% (62.00% CI95) in the state of Veracruz to 51.2% (64.36% CI95) in the Yucata´n peninsula and 14.5% (62.23% CI95) in and around Tapachula in the state of Chiapas. Spatial heterogeneity was also evident at smaller geographic scales. For example within the city of Chetumal, Quintana Roo, Ile1,016 frequencies varied from 38.3%–88.3%. A linear regression analysis based on seven collections from 2007 revealed that the frequency of Ile1,016 homozygotes accurately predicted knockdown rate for mosquitoes exposed to permethrin in a bioassay (R2 = 0.98). Conclusions: We have recorded a dramatic increase in the frequency of the Ile1,016 mutation in the voltage-gated sodium channel gene of Ae. aegypti in Me´xico from 1996 to 2009. This may be related to heavy use of permethrin-based insecticides in mosquito control programs. Spatial heterogeneity in Ile1,016 frequencies in 2007 and 2008 collections may reflect differences in selection pressure or in the initial frequency of Ile1,016. The rapid recent increase in Ile1,016 is predicted by a simple model of positive directional selection on a recessive allele. Unfortunately this model also predicts rapid fixation of Ile1,016 unless there is negative fitness associated with Ile1,016 in the absence of permethrin. If so, then spatial refugia of susceptible Ae. aegypti or rotational schedules of different classes of adulticides could be established to slow or prevent fixation of Ile1,016.